Mechanochemically carbonated clay, method for production thereof and use thereof

Through the method of mechanochemical carbonated clay, CO2 capture technology is reacted with clay precursors to generate mechanochemical carbonated clay with high CO2 content, solving the problem of difficulty in developing affordable fillers in the prior art without affecting concrete characteristics, achieving improvements in the compressive strength and durability of concrete, and at the same time reducing CO2 emissions.

CN119894843APending Publication Date: 2025-04-25CARBON UPCYCLING TECH INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380066029.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-17
Filing Date
2023-08-16
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to develop an affordable filler without affecting concrete properties, which can reduce CO2 emissions caused by cement production and combine CO2 capture technology to reduce environmental impact.

Method used

By using the method of mechanochemical carbonated clay, CO2 is reacted with clay precursors using CO2 capture technology to generate mechanochemical carbonated clay with high CO2 content and used it as a filler for concrete.

Benefits of technology

It improves the compressive strength and durability of concrete, while reducing water demand and chloride permeability, achieving an effective reduction of CO2 emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005310556620000261
    Figure BDA0005310556620000261
Patent Text Reader

Abstract

The invention relates to mechanochemical carbonated clay. The invention further relates to a method for the production thereof and to the use thereof. The invention further relates to compositions comprising the mechanochemically carbonated clay and an additional material selected from the group consisting of bitumen, cement, polymers and combinations thereof. The invention further relates to concrete and a preparation method thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a mechanochemically carbonated clay. The present invention further relates to a method for its production and its use. The present invention further relates to a composition comprising the mechanochemically carbonated clay and an additional material selected from the group consisting of asphalt, cement, geopolymers, polymers and combinations thereof. The present invention further relates to concrete and a method for its preparation. Background Art

[0002] Concrete is a composite material comprising a matrix of aggregate (typically rock material) and a binder (typically Portland cement or asphalt) that holds the matrix together. Concrete is one of the most commonly used building materials and is said to be the second most widely used material on earth after water.

[0003] In order to reduce the cost of concrete and the CO2 emissions generated by global cement production, a great deal of research effort has been devoted to identifying inexpensive materials that can be used as fillers or alternative binders to replace the binder component without (detrimentally) affecting the properties of concrete. Such secondary cementitious materials are an area of ​​wide industrial interest.

[0004] An example of a widely used cementitious filler is limestone. A comprehensive overview of fillers in cementitious materials can be found in John, Vanderley M., et al. "Fillers in cementitious materials-Experience, recent advances and future potential." Cement and Concrete Research 114 (2018): 65-78.

[0005] The production of Portland cement constitutes about 8% of the world's CO2 emissions. According to Vanderley et al., traditional mitigation strategies for CO2 emissions in the cement industry are insufficient to ensure the necessary mitigation in the face of increasing cement demand. Currently, cement production is increasing due to a combination of increasing urbanization and replacement of old infrastructure. Therefore, the adoption of expensive and environmentally risky carbon capture and storage (CCS) has been recognized by cement industry leaders as an inevitable solution.

[0006] Therefore, there remains a need to develop affordable filler technologies that can combine both the CO2 emission reductions achieved through reduced cement production and the CO2 emission reductions achieved through carbon capture technologies and that do not adversely affect the properties of concrete.

[0007] US 2012 / 0055376 A1 describes reducing CO2 emissions from concrete by partially replacing cement with a supplementary cementitious material comprising calcined clay and ground carbonate material.

[0008] It is an object of the present invention to provide an improved filler for cement, geopolymer or bituminous binders.

[0009] A further object of the present invention is to provide improved fillers for cement, geopolymer or bituminous binders which are inexpensive to produce.

[0010] It is a further object of the present invention to provide improved fillers for cement, geopolymer or asphalt binders, which fillers are produced using CO2 capture technology.

[0011] A further object of the present invention is to provide improved fillers for cement, geopolymer or bituminous binders which improve the properties of the resulting concrete, such as compressive strength, strength activity index and / or water demand. Summary of the invention

[0012] In a first aspect, the present invention provides a mechanochemically carbonated clay preferably having a carbonation temperature of less than 50 m 2 / g specific surface area and is preferably obtainable by carbonation of a clay precursor, wherein the ratio of the CO2 content of the mechanochemically carbonated clay to the CO2 content of the clay precursor is at least 1.1:1, preferably at least 1.15:1, more preferably at least 1.2:1, wherein the CO2 content is determined as the mass loss above 450°C measured by TGA using a temperature trace in which the temperature is increased from room temperature to 800°C at a rate of 10°C / min; and / or • The ratio of the total carbon content of the mechanochemically carbonated clay to the total carbon content of the clay precursor is at least 1.3:1, more preferably at least 1.35:1.

[0013] VIZCAYNO C et al.: "Pozzolan obtained by mechanochemical and thermal treatments of kaolin" APPLIED CLAYSCIENCE, ELSEVIER, Amsterdam, The Netherlands, Vol. 49, No. 4, 1 August 2010, pp. 405-413, describes grinding kaolin in an air atmosphere to increase its pozzolanic activity. As shown in the accompanying examples, e.g., Comparative Example C1 (involving calcined air-milled clay) and Comparative Example D1 (non-calcined air-milled clay), the carbonated clay of the present invention has unexpectedly and strongly improved strength activity index at 7 and 28 days compared to calcined and / or air-milled clay.

[0014] In another aspect, the present invention provides a method for producing mechanochemically carbonated clay, the method comprising the steps of: a) providing a raw material comprising or consisting of a clay precursor; b) providing a gas comprising CO2, preferably comprising at least 0.5% by volume CO2; c) introducing the raw material and the gas into a mechanical stirring unit; and d) subjecting the feedstock material to a mechanical stirring operation in the presence of the gas in the mechanical stirring unit.

[0015] The feedstock is preferably solid, so that the present invention provides a method for producing mechanochemically carbonated clay, the method comprising the steps of: a) providing a solid feedstock comprising or consisting of a clay precursor; b) providing a gas comprising CO2, preferably comprising at least 0.5% by volume CO2; c) introducing the solid feedstock and the gas into a mechanical stirring unit; and d) subjecting the solid feedstock material to a mechanical stirring operation in the presence of the gas in the mechanical stirring unit to obtain mechanochemically carbonated clay.

[0016] This method can be applied to various types of clay precursors, advantageously producing unique mechanochemically carbonated clays.

[0017] In another aspect, the present invention provides a mechanochemically carbonated clay obtainable by the method for producing a mechanochemically carbonated clay as described herein.

[0018] As will be shown in the accompanying examples, it was found that when such mechanochemically carbonated clays as described herein are used as fillers in cement, the compressive strength of the resulting concrete unexpectedly increases beyond the values ​​obtained for non-carbonated clays and in particular far exceeds the values ​​of pure Portland cement. In particular, the curing time for strength development is strongly improved (shortened) compared to when non-mechanically carbonated clays are used as fillers. Furthermore, much higher amounts of this mechanochemically carbonated clay can be used as fillers while also producing acceptable or even improved concrete properties.

[0019] It was also found that the durability of concrete produced using the mechanochemically carbonated clay was greatly increased. Without wishing to be bound by any theory, the inventors of the present invention believe that this is due to enhanced micro- and sub-micro-scale hydration, reduced chloride permeability, reduced concrete porosity and / or passivation of free lime. Furthermore, the increased oxygen content may lead to better dispersion in polar solvents and better compatibility with materials having epoxy or carboxyl functional groups compared to untreated precursors or feedstocks.

[0020] In addition, as shown in the attached examples, compared with pure cement and compared with the cement filled with non-carbonated clay, water demand is reduced. In view of the reduction of the particle size of mechanochemical carbonated clay compared with non-carbonated clay, this is particularly unexpected. Reduced particle size is usually associated with increased water demand. As compared with untreated raw materials or pure cement, the reduced water demand can contribute to improved characteristics, such as workability, compressive strength, permeability, water tightness, durability, weather resistance, drying shrinkage and the possibility of cracking. For these reasons, the amount of water in the limit and control concrete is important for both workability and service life. Therefore, the present invention allows better control of water demand. Without wishing to be bound by any theory, it is believed that when analyzed by XRD, the mechanochemical method of the present invention can cause the increase of amorphous content, wherein at least some crystalline domains that can be present in the raw material are maintained in the form of microcrystallinity via internal structure, and the form of this microcrystallinity persists in more general disordered structure. Therefore, this disordered macrostructure promotes higher reactivity and improves cement hydration.

[0021] Furthermore, the production of the mechanochemically carbonated clays relies on an inexpensive CO2 capture technology platform that is capable of operating on dilute CO2 streams, such as directly on point source emissions from combustion equipment, providing a filler that can be produced in an economically viable manner and combines both the CO2 emission reductions achieved by reducing cement production and the CO2 emission reductions achieved by CO2 sequestration. Thus, the mechanochemically carbonated clays of the present invention, and in particular the mechanochemically carbonated clays of the present invention, constitute excellent fillers for many applications, combining different mechanical properties with cost-effective CO2 capture technology.

[0022] In another aspect, the present invention provides a composition comprising the mechanochemically carbonated clay as described herein and an additional material selected from the group consisting of asphalt, geopolymers, cement, polymers, and combinations thereof.

[0023] In another aspect, the present invention provides a method for preparing a composition as described herein, comprising the steps of: (i) providing a mechanochemically carbonated clay as described herein; (ii) providing an additional material selected from the group consisting of asphalt, geopolymer, cement, polymer and combinations thereof; and (iii) combining the mechanochemically carbonated clay of step (i) with the material of step (ii).

[0024] In another aspect, the present invention provides a method for preparing concrete or mortar, the method comprising the steps of: (i) providing a mechanochemically carbonated clay as described herein and an additional material selected from the group consisting of asphalt, cement, geopolymers and combinations thereof, optionally in the form of a composition as described herein, wherein the additional material is selected from the group consisting of asphalt, cement, geopolymers and combinations thereof; (ii) supply of construction aggregates; and (iii) contacting, preferably mixing, the mechanochemically carbonated clay of step (i) and the additional materials with the building aggregate of step (ii) and optionally water.

[0025] In another aspect, the present invention provides concrete or mortar obtainable by the method for preparing concrete as described herein.

[0026] In another aspect, the present invention provides the use of a mechanochemically carbonated clay as described herein: as a filler, preferably as a filler in a material selected from the group consisting of bitumen, geopolymers, cement, mortar, polymers and combinations thereof; As a partial replacement for asphalt, geopolymer or cement in concrete or mortar; Increase the compressive strength of concrete or mortar; Improve the durability of concrete or mortar; ·Reduce concrete expansion; Improve the durability of concrete or mortar by reducing chloride permeability and / or porosity; Improve the strength activity index of concrete or mortar; and / or Reduce the water demand of concrete or mortar, Preferably, · Simultaneously improve the strength activity index of concrete and reduce the water demand of concrete; or · Simultaneously improve the strength activity index of the mortar and reduce the water demand of the mortar. DETAILED DESCRIPTION

[0027] As used herein, the expression "comprise" and variations thereof, such as "comprises" and "comprising", should be interpreted in an open, inclusive sense, meaning that the described embodiments include the recited features, but it does not exclude the presence of other features as long as they do not render the embodiment inoperable.

[0028] As used herein, the expressions "one embodiment," "specific embodiment," "embodiment," etc. should be interpreted as meaning that a particular feature, structure, or characteristic described in conjunction with the embodiment is included in at least one embodiment. Therefore, the appearance of such expressions in various places throughout this specification does not necessarily refer to the same embodiment. In addition, in one or more embodiments, the particular features, structures, or characteristics may be combined in any suitable manner. For example, certain features of the present disclosure described herein in the context of separate embodiments are also expressly contemplated in combination in a single embodiment.

[0029] Unless the context clearly dictates otherwise, as used herein, the singular forms "a / an" and "the" should be construed to include plural referents. It should also be noted that the term "or" is generally employed in its broadest sense, i.e., meaning "and / or", unless the context clearly dictates otherwise.

[0030] Whenever throughout this document a compound is mentioned as a salt, this should be interpreted as including the anhydrous form of the compound as well as any solvates (especially hydrates).

[0031] The terms "clay precursor" and "clay" as used herein should be interpreted as a solid material comprising at least 50 wt.% of a hydrated aluminum phyllosilicate, preferably at least 75 wt.% of a hydrated aluminum phyllosilicate, more preferably at least 90 wt.% of a hydrated aluminum phyllosilicate. The hydrated aluminum phyllosilicate is preferably selected from the kaolin family, the montmorillonite family, the vermiculite family, or a mixture thereof. The clay may be calcined or non-calcined.

[0032] The term "mechanochemically carbonated clay" is used herein to refer to the clay obtainable by the mechanochemical carbonation process of the present invention.

[0033] According to the present invention, the BET surface area as referred to herein is determined at a temperature of 77 K using a sample mass of 0.1-0.5 g. The BET surface area as referred to herein is determined using nitrogen. A preferred analytical method for determining the BET surface area comprises heating the sample to 400° C. for a desorption cycle prior to the surface area analysis. A suitable and therefore preferred analytical device for determining the BET surface area is a Micromeritics Gemini VII 2390 surface analyzer preferably equipped with a Micromeritics FlowPrep 060 flow gas degassing unit.

[0034] As used herein, TGA refers to thermogravimetric analysis, a technique known to those skilled in the art. A preferred TGA setting for determining the CO content of raw materials and carbonating materials in the context of the present invention is a Setaram TAG 16TGA / DSC dual chamber balance, using a 0.1-2 mg sample. According to the present invention, TGA is carried out under an inert atmosphere such as nitrogen or argon.

[0035] According to the present invention, the particle size distribution characteristics such as D10, D50 and D90 and specific surface area (unless explicitly mentioned as BET surface area) mentioned herein are measured using the Fraunhofer theory of light scattering with a laser scattering particle size analyzer (such as Brookhaven laser particle size analyzer, model Microbrook 2000LD or other instruments with equal or better sensitivity) and the data are reported using the volume equivalent sphere model. As known to the skilled person, D50 is the mass median diameter, that is, the diameter at which 50% of the sample mass is composed of smaller particles. Similarly, D10 and D90 represent the diameter at which 10% or 90% of the sample mass is composed of smaller particles.

[0036] The total carbon (TC) content referred to herein is preferably determined according to the method described in Soil Sampling and Methods of Analysis, 2nd Edition, CRC Press (2008), p. 244 et seq., which is incorporated herein by reference. The total carbon (TC) content is always expressed herein as wt.% based on the total weight of the measured composition (i.e., based on the total weight of the clay precursor, or based on the total weight of the carbonated clay).

[0037] According to the present invention, the compressive strength, strength-activity index and water demand as referred to herein are determined according to ASTM C311 / C311M-22. As will be apparent to the skilled person, when conducting these tests, the clay precursor or carbonated clay of the present invention is used instead of the "fly ash or natural pozzolan" specified by the standard.

[0038] For purposes of this disclosure, the ideal gas law is assumed such that volume % of a gas is considered equal to mol %. Mechanochemical Carbonation of Clay

[0039] In a first aspect, the present invention provides a mechanochemically carbonated clay preferably having a carbonation temperature of less than 50 m 2 / g specific surface area. The mechanochemically carbonated clay preferably has a CO2 content greater than 0.8 wt.% (based on the total weight of the mechanochemically carbonated clay), preferably greater than 1 wt.% (based on the total weight of the mechanochemically carbonated clay), more preferably greater than 1.5 wt.% (based on the total weight of the mechanochemically carbonated clay), wherein the CO2 content is determined as the mass loss above 450°C measured by TGA using a temperature trace, wherein the temperature is increased from room temperature to 800°C at a rate of 10°C / min. The mechanochemically carbonated clay is obtainable by carbonation of a clay precursor.

[0040] In a preferred embodiment, the mechanochemically carbonated clay meets the strength requirements set forth in ASTM C618-12a (2012).

[0041] In a preferred embodiment of the present invention, the mechanochemically carbonated clay has a carbonation temperature of at least 0.6 m 2 / g, preferably at least 0.7m 2 / g, more preferably at least 0.8m 2 / g specific surface area.

[0042] In a preferred embodiment of the present invention, the mechanochemically carbonated clay has a carbonation temperature of less than 50 m 2 / g, preferably less than 30m 2 / g, more preferably less than 15m 2 For example, mechanochemically carbonated clays have a specific surface area of ​​up to 50 m 2 / g, up to 48m 2 / g, up to 46m 2 / g, up to 44m 2 / g, up to 42m 2 / g, up to 40m 2 / g, up to 38m 2 / g, up to 36m 2 / g, up to 34m 2 / g, up to 32m 2 / g, up to 30m 2 / g, up to 28m 2 / g, up to 26m 2 / g, up to 24m 2 / g, up to 22m 2 / g, up to 20m2 / g, up to 18m 2 / g, up to 16m 2 / g, up to 15m 2 / g, up to 12m 2 / g, up to 10m 2 / g, up to 8m 2 / g, up to 6m 2 / g, up to 4m 2 / g, up to 2m 2 / g and other specific surface areas.

[0043] In a highly preferred embodiment of the present invention, the mechanochemically carbonated clay has a carbonation temperature of less than 5 m 2 / g, preferably less than 3m 2 / g, more preferably less than 2m 2 For example, mechanochemically carbonated clay has a specific surface area of ​​less than 5.0 m 2 / g, less than 4.5m 2 / g, less than 4.0m 2 / g, less than 3.5m 2 / g, less than 3.0m 2 / g, less than 2.5m 2 / g, less than 2.0m 2 / g, less than 1.5m 2 / g and other specific surface areas.

[0044] The inventors have observed that mechanochemically carbonated clays having a specific surface area within the ranges specified herein have specific properties when considering performance, processing, etc., compared to untreated precursors or even carbonated materials having other surface areas. Thus, according to highly preferred embodiments of the present invention, the mechanochemically carbonated clay has a specific surface area in the region defined by the upper and lower bounds described herein, such as in the range of 0.3-50 m 2 / g, preferably 0.3-30m 2 / g, more preferably 0.3-10m 2 / g in the range of specific surface area; 0.4-50m 2 / g, preferably 0.4-30m 2 / g, more preferably 0.4-10m 2 / g in the range of specific surface area; 0.5-50m 2 / g, preferably 0.5-30m 2 / g, more preferably 0.5-10m 2 / g in the range of specific surface area; 0.3-5.0m 2 / g, preferably 0.3-3.0m 2 / g, more preferably 0.3-2.0m 2 / g in the range of specific surface area; 0.4-5.0m 2 / g, preferably 0.4-3.0m 2 / g, more preferably 0.4-2.0m 2 / g in the range of specific surface area; 0.5-5.0m 2 / g, preferably 0.5-3.0m 2 / g, more preferably 0.5-2.0m 2 / g range of specific surface area, etc.

[0045] In an embodiment of the present invention, the mechanochemically carbonated clay has one, two, or three, preferably three, of the following characteristics: D10 in the range of 0.005-3 μm, preferably 0.01-2 μm, most preferably 0.1-1.4 μm; D50 in the range of 0.1-30 μm, preferably 0.5-15 μm, most preferably 1-10 μm; • D90 in the range of 0.5-100 μm, preferably 1-80 μm, most preferably 5-70 μm.

[0046] In an embodiment of the present invention, there is provided a mechanochemically carbonated clay as described herein obtainable by simultaneous carbonation and size reduction of a clay precursor, wherein the ratio of the D50 of the mechanochemically carbonated clay to the D50 of the clay precursor is less than 0.5:1, preferably less than 0.1:1, more preferably less than 0.05:1.

[0047] In an embodiment of the present invention, the mechanochemically carbonated clay has a total carbon content of at least 0.75wt.%, preferably at least 0.85wt.%, more preferably at least 0.9wt.%. The inventors have observed that a mechanochemically carbonated clay having a total carbon content of at least 1wt.%, preferably at least 1.5wt.%, more preferably at least 2wt.% provides even better results. Therefore, in a preferred embodiment, the mechanochemically carbonated clay has a total carbon content of at least 1wt.%, preferably at least 1.5wt.%, more preferably at least 2wt.%, providing even better results. Preferably, the mechanochemically carbonated clay is obtainable by carbonation of a clay precursor, wherein the ratio of the total carbon content of the mechanochemically carbonated clay to the total carbon content of the clay precursor is at least 1.3:1, more preferably at least 1.35:1. The inventors have observed that a method wherein the ratio is at least 1.4:1, preferably at least 1.6:1, more preferably at least 1.8:1 provides even better results, making these preferred. Similarly, the mechanochemically carbonated clay is preferably obtainable by carbonation of a clay precursor, wherein the ratio of the CO2 content of the mechanochemically carbonated clay to the CO2 content of the clay precursor is at least 1.1:1, preferably at least 1.15:1, more preferably at least 1.2:1, wherein the CO2 content is determined as a mass loss above 450°C measured by TGA using a temperature trace, wherein the temperature is increased from room temperature to 800°C at a rate of 10°C / min. More preferably, the ratio of the CO2 content of the mechanochemically carbonated clay to the CO2 content of the clay precursor is at least 1.5:1, preferably at least 1.75:1, more preferably at least 2:1, wherein the CO2 content is determined as a mass loss above 450°C measured by TGA using a temperature trace, wherein the temperature is increased from room temperature to 800°C at a rate of 10°C / min.

[0048] Without wishing to be bound by any theory, the inventors of the present invention believe that the increase in specific surface area achieved by the dry mechanochemical carbonation method of another aspect of the present invention (which is described elsewhere herein) is associated with the observed beneficial properties (such as excellent strength activity index and reduced water demand). Therefore, in an embodiment of the present invention, there is provided a mechanochemically carbonated clay as described herein obtainable by simultaneous carbonation and increase in specific surface area of ​​a clay precursor, wherein the ratio of the specific surface area of ​​the mechanochemically carbonated clay to the specific surface area of ​​the clay precursor is at least 1.2:1, preferably at least 1.4:1, and more preferably at least 1.6:1.

[0049] Without wishing to be bound by any theory, the inventors of the present invention believe that the increase in BET surface area achieved by the dry mechanochemical carbonation method of another aspect of the present invention (which is described elsewhere herein) is associated with the observed beneficial properties (such as excellent strength activity index and reduced water demand). Therefore, in an embodiment of the present invention, there is provided a mechanochemically carbonated clay as described herein obtainable by simultaneous carbonation and BET surface area increase of a clay precursor, wherein the ratio of the BET surface area of ​​the mechanochemically carbonated clay to the BET surface area of ​​the clay precursor is at least 2:1, preferably at least 3:1, more preferably at least 3.5:1.

[0050] Without wishing to be bound by any theory, the inventors of the present invention believe that the increase in BET surface area achieved by the dry mechanochemical carbonation method of another aspect of the present invention (which is described elsewhere herein) can be largely attributed to the increase in the number of pores observed by the reduction in average pore width and the increase in total pore surface area. Therefore, in an embodiment of the present invention, a mechanochemically carbonated clay obtainable by simultaneous carbonation and BET surface area increase of a clay precursor is provided, wherein the BJH desorption cumulative surface area of ​​the pores of the mechanochemically carbonated clay is at least 110%, preferably at least 120%, more preferably at least 150% of the BJH desorption cumulative surface area of ​​the pores of the clay precursor, and the desorption average pore width (4V / A obtained by BET) of the mechanochemically carbonated clay is no more than 90%, preferably no more than 85%, more preferably no more than 80% of the desorption average pore width (4V / A obtained by BET) of the clay precursor.

[0051] According to the present invention, the mechanochemically carbonated clay typically has a strength activity index (SAI) of at least 75%, preferably at least 80% at day 7. The inventors have observed that the mechanochemical process of the present invention allows to obtain carbonated clays with excellent SAI at day 7. Thus, in a preferred embodiment, the mechanochemically carbonated clay has a SAI of at least 105%, preferably at least 110%, even more preferably at least 125% at day 7.

[0052] In an embodiment of the present invention, the mechanochemically carbonated clay has a strength activity index (SAI) of at least 75%, preferably at least 95%, more preferably at least 100% at day 28. The inventors have observed that the mechanochemical process of the present invention allows to obtain carbonated clays with excellent SAI at day 28. Therefore, in a preferred embodiment, the mechanochemically carbonated clay has a SAI of at least 110%, preferably at least 115%, even more preferably at least 125% at day 28.

[0053] In an embodiment of the present invention, the mechanochemically carbonated clay has a water demand of less than 97%, preferably less than 96%, more preferably less than 95%. The inventors have observed that the mechanochemical process of the present invention allows to obtain carbonated clays with very low water demand. Therefore, in a preferred embodiment, the mechanochemically carbonated clay has a water demand of less than 93%, preferably less than 91%. In a preferred embodiment of the present invention, the clay precursor contains CaO and / or Ca(OH)2, preferably the clay precursor contains at least 0.1 wt.% (based on the total weight of the clay precursor) of CaO and / or Ca(OH)2, preferably at least 0.5 wt.% (based on the total weight of the clay precursor) of CaO and / or Ca(OH)2. Process for producing mechanochemically carbonated clay and mechanochemically carbonated clay obtainable therefrom

[0054] Without wishing to be bound by any theory, the inventors of the present invention believe that the dry mechanochemical carbonation process of the present invention imparts unique and desirable properties to the carbonated clay obtainable by the process. For example, it is believed that the unique surface area and pore characteristics achieved by the dry mechanochemical carbonation process of the present invention are important in achieving the unexpected performance of the material in, for example, concrete.

[0055] In a further aspect, the present invention provides a method for producing mechanochemically carbonated clay, the method comprising the steps of: a) providing a raw material comprising or consisting of a clay precursor; b) providing a gas comprising CO2, preferably at least 0.5% by volume CO2; c) introducing the raw material and the gas into a mechanical stirring unit; and d) subjecting the raw material material to a mechanical stirring operation in the presence of the gas in the mechanical stirring unit to obtain mechanochemically carbonated clay.

[0056] The feedstock is preferably a solid feedstock, so that the present invention highly preferably provides a method for producing mechanochemically carbonated clay comprising the steps of: a) providing a solid feedstock comprising or consisting of a clay precursor; b) providing a gas comprising CO2, preferably at least 0.5% by volume CO2; c) introducing the solid feedstock and the gas into a mechanical stirring unit; and d) subjecting the solid feedstock material to a mechanical stirring operation in the presence of the gas in the mechanical stirring unit to obtain mechanochemically carbonated clay. Method Description

[0057] The term "raw material" should be interpreted as a material consisting of or containing a clay precursor. Clay can be mixed with other materials to form a raw material (e.g., as in the case when shale is used as a raw material) or it can be essentially composed of clay. The term "precursor" is used to indicate the clay before the clay is subjected to the mechanochemical carbonation of the present invention. However, preferably, the raw material is essentially composed of a clay precursor and optionally water, because this allows the process conditions to be optimized to achieve the desired carbonated clay properties without having to consider the properties of other materials present in the raw material.

[0058] Following the guidance provided in this disclosure, it is within the capabilities of one skilled in the art to adapt the relevant process parameters such that a mechanochemically carbonated clay having the properties described herein is obtained.

[0059] The gas provided in step (b) may be any gas stream comprising CO 2 , such as normal air, a waste gas stream having a low CO 2 concentration, or a concentrated CO 2 stream.

[0060] In embodiments of the methods described herein, the gas provided in step (b) is normal air.

[0061] In a highly preferred embodiment of the method described herein, the gas provided in step (b) is a combustion flue gas, particularly a flue gas from fossil fuel combustion, wood pellet combustion, biomass combustion or municipal waste combustion. The fossil fuel combustion can be coal, petroleum coke, oil, natural gas, shale oil, asphalt, tar sand oil or heavy oil combustion or any combination thereof. The combustion flue gas can optionally have been treated to reduce water content, SO2 content, and / or NOx content.

[0062] The CO2 concentration in the gas provided in step (b) is preferably at least 0.1 volume %, more preferably at least 0.5 volume %. Typical CO2 concentrations of combustion flue gases are in the range of 1 volume %-15 volume % (such as 2 volume %-10 volume %), so that it is preferred that the gas provided in step (b) has a CO2 concentration in the range of 1 volume %-15 volume % (such as 2 volume %-10 volume %). In alternative embodiments of the present invention, the gas provided in step (b) contains at least 80 volume % CO2, preferably at least 95 volume % CO2. In some embodiments of the present invention, the gas provided in step (b) contains at least 80 volume % CO2, preferably at least 95 volume % CO2 and less than 1000ppm (v / v) of H2O, preferably less than 100ppm (v / v) of H2O. In some embodiments, the gas provided in step (b) contains at least 0.1 volume % CO2 and H2O in the range of 5 volume %-25 volume %. For example, in the case of flue gas, the gas provided in step (b) preferably contains CO in the range of 1 volume %-15 volume % (such as 2 volume %-10 volume %) and H in the range of 5 volume %-25 volume % (such as 15 volume %-20 volume %) O. The gas is typically not in a supercritical state, because this is not necessary for the mild mechanochemical carbonation method of the present invention. Therefore, in any embodiment of the present invention, it is highly preferred that the gas is not in a supercritical state.

[0063] In some embodiments of the invention, the methods described herein provide that the temperature and pressure during step (d) are such that the pressure is below the saturated vapor pressure of water at the temperature in the mechanically agitated unit.

[0064] In step (d), the expression "in the presence of said gas" should be interpreted as meaning that the atmosphere inside the mechanical stirring unit at the start of step (d) consists essentially of the gas provided in step (b). The skilled person will understand that unless the reactor (mechanical stirring unit) is continuously purged or replenished, the composition of the gas will change as the reaction progresses.

[0065] Typically, step (d) can be carried out at atmospheric pressure, below atmospheric pressure or above atmospheric pressure. Typically, it is preferred that step (d) is carried out at atmospheric pressure or above atmospheric pressure. Therefore, it is preferred that step (d) is carried out at a pressure of at least about 100kPa (e.g., at least 101.325kPa). In a preferred embodiment of the present invention, step (d) is carried out at a pressure greater than about 300kPa (e.g., 303.975kPa), preferably greater than about 600kPa (e.g., 607.95kPa). In an alternative embodiment of the present invention, step (d) is carried out at a pressure less than about 100kPa (e.g., at least 101.325kPa), such as less than 50kPa or less than 10kPa. The technician will understand that (if not actively maintained) the pressure of the gas will change as the reaction progresses. In these embodiments, it should be understood that when step (d) is started, the pressure inside the mechanical stirring unit is as specified herein. In some embodiments, throughout most or substantially all of step (d), the pressure inside the mechanical stirring unit is as specified herein.

[0066] In the highly preferred embodiment of the method described herein, step (d) is carried out at a pressure lower than the critical pressure of carbon dioxide. In addition, the inventors have found that the preparation of the mechanochemical carbonated clay of the present invention does not require very high pressure, so that the method can be carried out in a very energy efficient manner. Therefore, preferably, step (d) is carried out at a pressure less than 10000kPa, preferably less than 5000kPa, more preferably less than 2500kPa and most preferably less than 1000kPa. The technician will understand that the pressure of the gas (if not actively maintained) will change as the reaction progresses. In these embodiments, it should be understood that at least one time point during step (d), for example, when step (d) is started, the pressure inside the mechanical agitation unit is as specified herein. In certain embodiments, in most or substantially all of running through step (d), the pressure inside the mechanical agitation unit is as specified herein.

[0067] In a highly preferred embodiment of the method described herein, in order to stimulate carbonation, step (d) is carried out at a temperature of less than 150°C, preferably less than 100°C, preferably less than 90°C, more preferably less than 80°C, most preferably less than 75°C. In a highly preferred embodiment of the invention, step (d) is carried out at a temperature in the range of 45°C-85°C, preferably 55°C-70°C. In a preferred embodiment of the invention, no active heating is applied and any increase in temperature is due to friction caused by mechanical agitation or to exothermic reactions occurring during mechanochemical carbonation. The temperature is preferably determined on the solid material in the reactor (i.e. the mechanical agitation unit) during processing.

[0068] In an embodiment of the invention, step (d) is performed for at least 1 minute, preferably at least 30 minutes, such as at least 1 hour, at least 4 hours, or at least 8 hours.

[0069] In a preferred embodiment of the present invention, step (d) is substantially free of CO2 solubilizers, such as glycerol (propane-1,2,3-triol). Such CO2 solubilizers function to enhance the solubility of carbon dioxide in aqueous solution and allow the formation of carbonic acid concentration for sequestration of carbon dioxide.

[0070] The low temperature requirement of the process of the present invention means that fossil fuels are not required, and electric heating means (or a green fuel source of low calorific value) can realistically be used to supply heat in cases where the friction caused by mechanical stirring is insufficient to reach the desired temperature (such as greater than 45° C.). In this way, fossil fuels can be avoided throughout the entire production chain.

[0071] As with any chemical process, the appropriate reaction time is highly dependent on the desired degree of carbonation, the desired surface area, and the applied pressure, temperature, and mechanochemical agitation, and can be readily determined by periodically sampling the material and monitoring the progress of the reaction, for example via BET analysis, particle size analysis, and total carbon determination as explained herein.

[0072] The inventors of the present invention have also found that the mechanochemical carbonation method described herein can be advantageously carried out without the use of additional oxidants such as acids. Therefore, the mechanochemical carbonation method described herein is preferably carried out without the use of strong acids, preferably without the use of any additional oxidants other than the gas provided in step (b).

[0073] In a preferred embodiment of the present invention, the mechanical stirring operation of step (d) comprises grinding, milling, mixing, stirring (such as low-speed stirring or high-speed stirring), shearing (such as high-torque shearing), vibration, blending, pulverizing, powdering, crushing, crushing, fluidized bed or ultrasonic treatment, preferably grinding, milling, mixing, stirring (such as low-speed stirring or high-speed stirring), shearing (such as high-torque shearing) or ultrasonic treatment. The inventors of the present invention have found that if the mechanochemical stirring operation of step (d), the mechanochemical stirring operation of step (d) is carried out in the presence of grinding or milling media, preferably balls or beads, then the mechanochemical carbonation method is promoted. Preferred materials are stainless steel or aluminum oxide. In such highly preferred embodiments of the present invention, the mechanical stirring operation can be a mechanical stirring unit that simply rotates a solid raw material, a grinding or milling media and a gas. For example, the grinding or milling media can be made of steel (e.g., AISI H13, modified H10), aluminum oxide, chrome white cast iron (e.g., ASTM A532), molybdenum steel (e.g., AISIM2, M4, M-42), chromium-based steel (e.g., H11, H12, H13 CPMV9, ZDP-189), or other media with a target HRC hardness of 60. Such grinding media can be utilized with or without surface treatments such as nitriding and carburizing. This can conveniently be performed in a rotating drum. It should be understood that when performed in a rotating drum, the products obtainable by the method of the present invention can also be obtainable using alternative grinding or milling techniques known to the skilled person.

[0074] In a preferred embodiment of the present invention, step (d) is carried out in the presence of a catalyst, preferably a metal oxide catalyst such as a transition metal oxide catalyst. Examples of suitable catalysts are selected from the group consisting of iron oxide, cobalt oxide, ruthenium oxide, titanium oxide, nickel oxide, aluminum oxide and combinations thereof.

[0075] Thus, as will be appreciated from the above, in a highly preferred embodiment of the invention, step (d) comprises grinding, milling, mixing, stirring (such as low speed stirring or high speed stirring), shearing (such as high torque shearing), shaking, blending, pulverizing, powdering, crushing, breaking, fluidizing bed or ultrasonic treatment, preferably grinding, milling, mixing, stirring (such as low speed stirring or high speed stirring), shearing (such as high torque shearing), or ultrasonic treatment in the presence of grinding or milling media and a metal oxide catalyst.

[0076] The inventors of the present invention have found that, considering the efficiency (such as reaction time, CO2 absorption and particle size reduction) of mechanochemical carbonation, it is advantageous to adopt a medium comprising (such as coated with) the metal oxide catalyst as described herein before and / or adopt a mechanical stirring unit (or part thereof) comprising (or coated with) the metal oxide catalyst, such as on one or more surfaces of contact raw materials during step (d). As explained elsewhere herein, the mechanical stirring operation can be a mechanical stirring unit that simply rotates the raw materials or clay precursors, grinding or milling media, metal oxide catalysts and gases for mechanochemical carbonation. This can be conveniently carried out in a rotating drum.

[0077] As will be clear from this specification, in highly preferred embodiments, step (d) is a substantially dry process. Although some moisture may be present and is beneficial for carbonation efficiency, step (d) is highly preferably not performed on an aqueous solution or slurry. The inventors of the present invention have found that performing step (d) on a solid greatly improves energy efficiency (since water does not have to be removed afterwards) and imparts unique properties to the resulting mechanochemically carbonated clay, resulting in a material that is substantially different from, for example, aqueous carbonated materials. This is also reflected in their different properties, for example when used as filler in concrete. In embodiments of the present invention, the solid raw material preferably has a moisture content of less than 30 wt.% (by total weight of the solid raw material), preferably less than 20 wt.%.

[0078] According to a highly preferred embodiment of the present invention, the raw material provided in step (a) is a solid raw material. The solid raw material provided in step (a) is highly preferably less than 30wt.% (by the total weight of the solid raw material), preferably less than 20wt.%, more preferably less than 15wt.% moisture content. Taking into account the carbonation efficiency, the solid raw material preferably has a moisture content of at least 2wt.% (by the total weight of the solid raw material), preferably at least 5wt.%, more preferably at least 10wt.%. At a moisture content of less than 30wt.% (by the total weight of the solid raw material), the raw material is still and behaves like a solid. In some embodiments of the present invention, the solid raw material may have a moisture content of less than 10wt.% (by the total weight of the solid raw material), less than 5wt.%, or less than 2wt.%. At least one time point during step (d), for example, when step (d) is started, the solid raw material preferably has the moisture content specified herein. In some embodiments, throughout most or substantially all of step (d), the moisture content of the raw material is as specified herein.

[0079] Adjusting the moisture content of the feedstock is within the routine capabilities of the skilled artisan based on the guidance provided herein (eg, by spraying the solid feedstock with an aqueous composition such as water before and / or during step (d)).

[0080] In other embodiments, the raw material provided in step (a) is an aqueous slurry, solution or suspension, such as an aqueous slurry. The aqueous slurry, solution or suspension raw material provided in step (a) can have a water content greater than 50wt.% (by the total weight of the aqueous slurry, solution or suspension raw material), for example greater than 70wt.%. At least one time point during step (d), for example when step (d) is started, the aqueous slurry, solution or suspension raw material preferably has a water content specified herein. In some embodiments, throughout most or substantially all of step (d), the water content of the aqueous slurry, solution or suspension raw material is as specified herein.

[0081] In some embodiments, step (d) is followed by a dehydration step to reduce the water content of the obtained mechanochemically carbonated glassy solid.

[0082] In particular, the inventors of the present invention have found that it is important to carry out step (d) such that In step (d) between , i.e. during the combined carbonation and mechanical agitation, a certain degree of carbonation, size reduction and / or surface area increase is achieved. This results in a material significantly different from, for example, a material that is ground and subsequently carbonated. In order to obtain these effects, it is preferred that the step (a) of the method comprises providing a solid raw material as described earlier herein, and step (d) is carried out on the solid raw material provided in step (a).

[0083] Thus, in a highly preferred embodiment of the present invention, there is provided a process of the present invention wherein carbonation, size reduction and / or surface area increase is achieved during step (d) such that the process has one, two, or all three, preferably all three, of the following features: the ratio of the CO2 content of the mechanochemically carbonated clay obtained in step (d) to the CO2 content of the clay precursor of step (a) is at least 1.1:1, preferably at least 1.15:1, more preferably at least 1.2:1, wherein the CO2 content is determined as the mass loss above 450°C measured by TGA using a temperature trace in which the temperature is increased from room temperature to 800°C at a rate of 10°C / min; The ratio of the D50 of the mechanochemically carbonated clay obtained in step (d) to the D50 of the clay precursor of step (a) is less than 0.9:1, preferably less than 0.85:1, more preferably less than 0.8:1; • The ratio of the specific surface area of ​​the mechanochemically carbonated clay obtained in step (d) to the specific surface area of ​​the clay precursor of step (a) is at least 1.15:1, preferably at least 1.2:1, more preferably at least 1.25:1.

[0084] As shown in the examples, certain materials have additional improved strength and / or water demand characteristics. Thus, in some particularly preferred embodiments of the present invention, a method of the present invention is provided wherein carbonation, size reduction and / or surface area increase is achieved during step (d) such that the method has one, two, or all three, preferably all three of the following characteristics: the ratio of the CO2 content of the mechanochemically carbonated clay obtained in step (d) to the CO2 content of the clay precursor of step (a) is at least 1.5:1, preferably at least 1.75:1, more preferably at least 2:1, wherein the CO2 content is determined as the mass loss above 450°C measured by TGA using a temperature trace in which the temperature is increased from room temperature to 800°C at a rate of 10°C / min; The ratio of the D50 of the mechanochemically carbonated clay obtained in step (d) to the D50 of the clay precursor of step (a) is less than 0.8:1, preferably less than 0.75:1, more preferably less than 0.1:1; • The ratio of the specific surface area of ​​the mechanochemically carbonated clay obtained in step (d) to the specific surface area of ​​the clay precursor of step (a) is at least 2:1, preferably at least 5:1, more preferably at least 10:1.

[0085] The inventors have observed that it is preferred to provide a process of the present invention wherein carbonation is achieved during step (d) such that the ratio of the total carbon content of the mechanochemically carbonated clay obtained in step (d) to the total carbon content of the clay precursor of step (a) is at least 1.3: 1, more preferably at least 1.35: 1. The inventors have observed that processes wherein the ratio is at least 1.4: 1, preferably at least 1.6: 1, more preferably at least 1.8: 1 provide even better results, making these preferred.

[0086] Without wishing to be bound by any theory, the inventors of the present invention believe that the increase in BET surface area achieved by the dry mechanochemical carbonation process is associated with the observed beneficial properties (such as excellent strength activity index and reduced water demand). Therefore, in a highly preferred embodiment of the present invention, a method of the present invention is provided, wherein carbonation and BET surface area increase are achieved during step (d) such that the ratio of the BET surface area of ​​the mechanochemically carbonated clay to the BET surface area of ​​the clay precursor is at least 2:1, preferably at least 3:1, more preferably at least 3.5:1.

[0087] The skilled person will appreciate that when the material of step (a) is fed to step (d), this means that the carbonation, size reduction and / or surface area specified above During step (d) accomplish.

[0088] In a particularly preferred embodiment of the method of the present invention, the BJH desorption cumulative surface area of ​​the pores of the mechanochemically carbonated clay obtained in step (d) is at least 110%, preferably at least 120%, more preferably at least 150% of the BJH desorption cumulative surface area of ​​the pores of the clay precursor, and the desorption average pore width (4V / A obtained by BET) of the mechanochemically carbonated clay obtained in step (d) is no more than 90%, preferably no more than 85%, more preferably no more than 80% of the desorption average pore width (4V / A obtained by BET) of the clay precursor.

[0089] In an embodiment of the present invention, the method described herein does not include a solid-liquid separation step selected from filtration, decantation and gravity separation (e.g., using a cyclone separator) after step (d), and preferably the method of the present invention does not include any solid-liquid separation step after step (d).

[0090] In embodiments of the invention, the methods described herein do not comprise a size selection step, such as a screening or sieving step, after step (d). Characteristics of the clay precursor used in the mechanochemical carbonation process of the present invention

[0091] In a preferred embodiment of the method described herein, the clay precursor is a material having a particle size of less than 20 μm. 2 / g, preferably less than 10m 2 / g, more preferably less than 2m 2 / g of particulate solid material.

[0092] In highly preferred embodiments of the invention, the clay precursor has one, two, or three, preferably three, of the following characteristics: D10 in the range of 0.1-50 μm, preferably 0.1-20 μm, most preferably 0.1-10 μm; D50 in the range of 5-200 μm, preferably 10-200 μm, most preferably 10-150 μm; • D90 in the range of 10-1000 μm, preferably 20-750 μm, most preferably 40-500 μm.

[0093] In a preferred embodiment of the present invention, the clay precursor contains CaO and / or Ca(OH)2, preferably the clay precursor contains at least 0.1 wt.% (based on the total weight of the clay precursor) of CaO and / or Ca(OH)2, preferably at least 0.5 wt.% (based on the total weight of the clay precursor) of CaO and / or Ca(OH)2. Characteristics of the mechanochemically carbonated clay obtained in step (d)

[0094] In a preferred embodiment of the process for producing carbonated clay described herein, the carbonated clay obtained in step (d) has a carbonation content of less than 50 m 2 The mechanochemically carbonated clay obtained in step (d) preferably has a CO2 content of greater than 0.8 wt.% (based on the total weight of the mechanochemically carbonated clay), preferably greater than 1 wt.% (based on the total weight of the mechanochemically carbonated clay), more preferably greater than 1.5 wt.% (based on the total weight of the mechanochemically carbonated clay), wherein the CO2 content is determined as the mass loss above 450°C measured by TGA using a temperature trace, wherein the temperature is increased from room temperature to 800°C at a rate of 10°C / min.

[0095] In a preferred embodiment, the mechanochemically carbonated clay obtained in step (d) meets the strength requirements set forth in ASTM C618-12a (2012). In a specific embodiment, the method described herein does not include a size selection step, such as a screening or sieving step, after step (d), and the carbonated clay obtained in step (d) meets the strength requirements set forth in ASTM C618-12a (2012).

[0096] In a preferred embodiment of the present invention, the mechanochemically carbonated clay obtained in step (d) has a carbonation temperature of at least 0.6 m 2 / g, preferably at least 0.7m 2 / g, more preferably at least 0.8m 2 / g specific surface area.

[0097] In a preferred embodiment of the present invention, the mechanochemically carbonated clay obtained in step (d) has a carbonation temperature of less than 50 m 2 / g, preferably less than 30m 2 / g, more preferably less than 15m 2 For example, the mechanochemically carbonated clay obtained in step (d) has a specific surface area of ​​at most 50 m 2 / g, up to 48m 2 / g, up to 46m 2 / g, up to 44m 2 / g, up to 42m2 / g, up to 40m 2 / g, up to 38m 2 / g, up to 36m 2 / g, up to 34m 2 / g, up to 32m 2 / g, up to 30m 2 / g, up to 28m 2 / g, up to 26m 2 / g, up to 24m 2 / g, up to 22m 2 / g, up to 20m 2 / g, up to 18m 2 / g, up to 16m 2 / g, up to 15m 2 / g, up to 12m 2 / g, up to 10m 2 / g, up to 8m 2 / g, up to 6m 2 / g, up to 4m 2 / g, up to 2m 2 / g and other specific surface areas.

[0098] In a highly preferred embodiment of the present invention, the mechanochemically carbonated clay obtained in step (d) has a carbonation temperature of less than 50 °C. 2 / g, preferably less than 3m 2 / g, more preferably less than 2m 2 For example, mechanochemically carbonated clay has a specific surface area of ​​less than 5.0 m 2 / g, less than 4.5m 2 / g, less than 4.0m 2 / g, less than 3.5m 2 / g, less than 3.0m 2 / g, less than 2.5m 2 / g, less than 2.0m 2 / g, less than 1.5m 2 / g and other specific surface areas.

[0099] The inventors have observed that mechanochemically carbonated clays having a specific surface area within the ranges specified herein have specific properties when considering properties, processing, etc., compared to untreated precursors or even carbonated materials having other surface areas. Thus, according to a highly preferred embodiment of the present invention, the mechanochemically carbonated clay obtained in step (d) has a specific surface area in the region defined by the upper and lower limits described herein, such as in the range of 0.6-50 m 2 / g, preferably 0.6-30m 2 / g, more preferably 0.6-10m 2 Specific surface area in the range of / g; between 0.8-50m 2 / g, preferably 0.8-30m 2 / g, more preferably 0.8-10m 2 / g in the range of specific surface area; in the range of 1-50m 2 / g, preferably 1-30m 2 / g, more preferably 1-10m 2 / g in the range of specific surface area; 0.6-5.0m 2 / g, preferably 0.6-3.0m 2 / g, more preferably 0.6-2.0m 2 / g in the range of specific surface area; 0.8-5.0m 2 / g, preferably 0.8-3.0m 2 / g, more preferably 0.8-2.0m 2 Specific surface area in the range of / g; between 1-5.0m 2 / g, preferably 1-3.0m 2 / g, more preferably 1-2.0m 2 / g range of specific surface area, etc.

[0100] In an embodiment of the present invention, the mechanochemically carbonated clay obtained in step (d) has one, two, or three, preferably three, of the following characteristics: D10 in the range of 0.005-3 μm, preferably 0.01-2 μm, most preferably 0.1-1.4 μm; D50 in the range of 0.1-30 μm, preferably 0.5-15 μm, most preferably 1-10 μm; • D90 in the range of 0.5-100 μm, preferably 1-80 μm, most preferably 5-70 μm.

[0101] In an embodiment of the present invention, the mechanochemically carbonated clay obtained in step (d) has a total carbon content of at least 0.75 wt.%, preferably at least 0.85 wt.%, more preferably at least 0.9 wt.%. The inventors have observed that a mechanochemically carbonated clay having a total carbon content of at least 1 wt.%, preferably at least 1.5 wt.%, more preferably at least 2 wt.% provides even better results. Therefore, in a preferred embodiment, the mechanochemically carbonated clay obtained in step (d) has a total carbon content of at least 1 wt.%, preferably at least 1.5 wt.%, more preferably at least 2 wt.%, providing even better results.

[0102] According to the present invention, the mechanochemically carbonated clay obtained in step (d) typically has a strength activity index (SAI) of at least 75%, preferably at least 80% at day 7. The inventors have observed that the mechanochemical process of the present invention allows to obtain carbonated clays with excellent SAI at day 7. Thus, in a preferred embodiment, the mechanochemically carbonated clay obtained in step (d) has a SAI of at least 105%, preferably at least 110%, even more preferably at least 125% at day 7.

[0103] In an embodiment of the present invention, the mechanochemically carbonated clay obtained in step (d) has a strength activity index (SAI) of at least 75%, preferably at least 95%, more preferably at least 100% at day 28. The inventors have observed that the mechanochemical process of the present invention allows to obtain carbonated clays with excellent SAI at day 28. Therefore, in a preferred embodiment, the mechanochemically carbonated clay obtained in step (d) has a SAI of at least 110%, preferably at least 115%, even more preferably at least 125% at day 28.

[0104] In an embodiment of the present invention, the mechanochemically carbonated clay obtained in step (d) has a water demand of less than 97%, preferably less than 96%, more preferably less than 95%. The inventors have observed that the mechanochemical process of the present invention allows to obtain carbonated clays with very low water demand. Therefore, in a preferred embodiment, the mechanochemically carbonated clay obtained in step (d) has a water demand of less than 93%, preferably less than 91%. Mechanochemically carbonated clay obtainable by the process described herein

[0105] The inventors of the present invention have found that the mechanochemical carbonation described herein imparts unique properties to the resulting mechanochemically carbonated clay, resulting in a material that is substantially different from, for example, aqueous carbonated materials. This is also reflected in their different properties, for example when used as filler in concrete. In particular, the inventors of the present invention have found that it is important to carry out step (d) such that During step (d) , i.e., during the combined carbonation and mechanical agitation, a certain degree of carbonation, size reduction and / or surface area increase is achieved. This results in a material that is significantly different from, for example, a material carbonated in an aqueous environment, or even a material that is ground and then carbonated.

[0106] Thus, in another aspect, the present invention provides a mechanochemically carbonated clay obtainable by the process for producing a mechanochemically carbonated clay as described herein.

[0107] As the skilled person will appreciate from this disclosure, the mechanochemically carbonated clays of the present invention constitute excellent fillers for many applications, combining different mechanical properties with a cost-effective CO2 sequestration method. Compositions comprising mechanochemically carbonated clay and methods of making the same

[0108] Thus, in another aspect, the present invention provides a composition comprising a mechanochemically carbonated clay as described herein and a further material selected from the group consisting of asphalt, cement, geopolymers, polymers and combinations thereof, preferably cement, more preferably Portland cement.

[0109] In an embodiment of the invention, the additional material is a polymer selected from thermoplastic polymers and thermosetting polymers. In a preferred embodiment of the invention, the additional component is a polymer selected from the group consisting of epoxy resins, phenolic resins, polyalkylene terephthalates (preferably polyethylene terephthalate), polyalkylene terephthalate adipates (preferably polybutylene terephthalate adipate), polyisosorbide alkylene terephthalates (preferably polyisosorbide ethylene terephthalate), polyalkylene aromatic polyamides (preferably polyethylene aromatic polyamides), polyacrylonitrile, polyacetal, polyimide, aromatic polyamides. Polyester, polyisoprene (preferably cis-1,4-polyisoprene), polyethylene, polypropylene, polyurethane, polyisocyanurate, polyamide, polyether, polyester, polyhydroxyalkanoate, polylactic acid, polylactic acid-co-glycolic acid, polyvinylidene fluoride, polyvinyl acetate, polyvinyl chloride, polystyrene, polytetrafluoroethylene, acrylonitrile-butadiene-styrene, nitrile rubber, styrene butadiene, ethylene-vinyl acetate, copolymers thereof and combinations thereof, more preferably polyolefins such as polypropylene, polyethylene, copolymers thereof and combinations thereof. The term "polymer" as used herein includes copolymers such as block copolymers.

[0110] In a highly preferred embodiment, the additional material is selected from cement, asphalt, geopolymers or combinations thereof.

[0111] According to the invention, the cement may be hydraulic or non-hydraulic cement. In a preferred embodiment of the invention, the cement is a hydraulic cement, such as Portland cement. In a highly preferred embodiment of the invention, the cement is one of the cements defined in EN 197-1 (2011), preferably Portland cement as defined in EN 197-1 (2011).

[0112] In an embodiment of the present invention, the composition comprises at least 0.1 wt.% (based on the total weight of the composition), preferably at least 1 wt.%, more preferably greater than 5 wt.% of mechanochemically carbonated clay and / or at least 0.1 wt.% (based on the total weight of the composition), preferably greater than 1 wt.%, more preferably greater than 20 wt.% of additional materials.

[0113] In an embodiment of the invention, the composition comprises less than 60 wt.% (based on the total weight of the composition), preferably less than 50 wt.%, more preferably less than 45 wt.% of mechanochemically carbonated clay and / or less than 95 wt.% (based on the total weight of the composition), preferably less than 90 wt.%, more preferably less than 80 wt.% of additional materials.

[0114] In an embodiment of the invention, a composition is provided wherein the weight:weight ratio of the mechanochemically carbonated clay to the additional material is in the range of 1:9 to 2:1, preferably in the range of 1:8 to 1:1, more preferably in the range of 1:6 to 5:6.

[0115] In an embodiment of the present invention, the composition comprises 5wt.%-70wt.% (based on the total weight of the composition), preferably 10wt.%-60wt.%, more preferably 20wt.%-50wt.% of mechanochemically carbonated clay and 30wt.%-95wt.% (based on the total weight of the composition), preferably 40wt.%-90wt.%, preferably 50wt.%-80wt.% of additional materials.

[0116] In an embodiment of the invention, the composition comprises less than 5 wt.% (based on the total weight of the composition), preferably less than 1 wt.%, more preferably less than 0.1 wt.% water. The amount of water can be suitably determined as the mass loss up to 120°C measured by TGAMS using a temperature trajectory, wherein the temperature is increased from room temperature to 800°C at a rate of 10°C / min.

[0117] In an embodiment of the invention, the composition consists of mechanochemically carbonated clay and additional materials.

[0118] In another aspect, the present invention provides a method for preparing a composition as described herein, comprising the steps of: (i) providing a mechanochemically carbonated clay as described herein, preferably a mechanochemically carbonated clay as described herein; (ii) providing an additional material selected from the group consisting of asphalt, cement, geopolymer, polymer, and combinations thereof; (iii) combining the mechanochemically carbonated clay solids of step (i) with the material of step (ii). Method for preparing concrete or mortar

[0119] Therefore, in another aspect, the present invention provides a method for preparing concrete or mortar, the method comprising the steps of: (i) providing a mechanochemically carbonated clay as described herein and an additional material selected from the group consisting of asphalt, cement, geopolymers and combinations thereof, optionally in the form of a composition as described herein, wherein the additional material is selected from the group consisting of asphalt, cement, geopolymers and combinations thereof; (ii) supply of construction aggregates; and (iii) contacting, preferably mixing, the mechanochemically carbonated clay of step (i) and the additional materials with the building aggregate of step (ii) and optionally water.

[0120] In another aspect, the present invention provides a concrete or mortar obtainable by the method for preparing concrete as described herein.

[0121] In a preferred embodiment of the present invention, step (iii) further comprises contacting, preferably mixing, the mechanochemically carbonated clay and additional materials of step (i) with the building aggregate and water of step (ii). According to the present invention, the mechanochemically carbonated clay and additional materials of step (i), the building aggregate and water of step (ii) may be contacted, preferably mixed, substantially simultaneously, or in a stepwise manner, wherein the composition of step (i) is first contacted, preferably mixed, with water and then contacted, preferably mixed, with the building aggregate of step (ii).

[0122] In another aspect, the present invention provides the use of a mechanochemically carbonated clay as described herein: as a filler, preferably as a filler in a material selected from the group consisting of asphalt, cement, geopolymer, mortar, polymer and combinations thereof; As a partial replacement for asphalt, geopolymer or cement in concrete or mortar; Increase the compressive strength of concrete or mortar; Improve the durability of concrete or mortar; Reduce the expansion of concrete; Improve the durability of concrete or mortar by reducing chloride permeability and / or porosity; Improve the strength activity index of concrete or mortar; and / or Reduce the water demand of concrete or mortar, Preferably, · Simultaneously improve the strength activity index of concrete and reduce the water demand of concrete; or · Simultaneously improve the strength activity index of the mortar and reduce the water demand of the mortar. Examples

[0123] The BET surface area (SSA), BJH desorption cumulative surface area of ​​the pores and the desorption average pore width (4 V / A obtained by BET) were determined at a temperature of 77 K using a sample mass of 0.5-1 g, where the samples were heated to 400 °C for the desorption cycle prior to the surface area analysis.

[0124] Particle size distribution and specific surface area measurements were performed on a Brookhaven laser particle size analyzer, model Microbrook 2000LD, using the Fraunhofer theory of light scattering, and data are reported using the volume equivalent sphere model.

[0125] Compressive strength, strength activity index and water demand are measured according to ASTM C311 / C311M-22. As will be apparent to the skilled person, when carrying out these tests, the clay precursors or carbonated clays of the invention are used in place of the "fly ash or natural pozzolan" specified by the standard.

[0126] The CO2 content was determined as the mass loss above 450°C as measured by TGA using a temperature trace where the temperature was increased from room temperature to 800°C at a rate of 10°C / min. A Setaram TAG 16 TGA / DSC dual chamber balance was used under an inert nitrogen atmosphere with 0.1-2 mg samples. Example 1 Sample A

[0127] Mechanochemically carbonated clay is produced by inserting 0.4 kg of clay precursor (non-calcined clay) into a pressure cell with 2 kg of first grinding media (one or more stainless steel ball bearings of 5 mm size) and 5 kg of second grinding media (one or more stainless steel ball bearings of 1 mm size). The cell is pressurized with concentrated CO2 gas and rotated on a roller at 65 RPM for 5 days to obtain mechanochemically carbonated clay. The clay precursor is used as is. The reaction is initiated at room temperature and no heating or cooling is applied. The characteristics of clay precursor (A1) and the mechanochemically carbonated clay (A2) obtained are shown in the following table. Sample B

[0128] Mechanochemically carbonated clay was produced by inserting 5 kg of clay precursor (calcined clay, from a different source than sample A) into a pressure chamber with 150 kg of grinding media (10 mm size ceramic bearings). The chamber was pressurized to an initial pressure of 448 kPa with flue gas (CO2: 8 vol%-10 vol%; H2O: 18 vol%-20 vol%; O2: 2 vol%-3 vol%; N2: 67 vol%-72 vol%) and rotated on a roller at 38 RPM for 3 days to obtain mechanochemically carbonated clay. The clay precursor was used as is. The reaction was initiated at room temperature and no heating or cooling was applied. The ceramic bearings had an Al2O3 content of 92 wt.%, so that they were also used as catalysts. The properties of the clay precursor (B1) and the obtained mechanochemically carbonated clay (B2) are shown in the following table. Sample C

[0129] Mechanochemically carbonated clay was produced by inserting 10 kg of clay precursor (calcined clay, from a different source than sample A or B) into a pressure chamber with 100 kg of grinding media (ceramic bearings of 25.4 mm size). The chamber was pressurized to an initial pressure of 441 kPa with flue gas (CO2: 8% by volume-10% by volume; H2O: 18% by volume-20% by volume; O2: 2% by volume-3% by volume; N2: 67% by volume-72% by volume) and rotated on a roller at 38 RPM for 2 days to obtain mechanochemically carbonated clay. The clay precursor was used as is. The reaction was initiated at room temperature and no heating or cooling was applied. The ceramic bearings had an Al2O3 content of 92 wt.%, so that they were also used as catalysts. A portion of the clay precursor was subjected to conventional milling for use as a comparative example. The properties of the milled clay precursor (C1) and the obtained mechanochemically carbonated clay (C2) are shown in the following table. Sample D

[0130] Mechanochemically carbonated clay was produced by inserting 5 kg of clay precursor (non-calcined clay, from the same source as sample C) into a pressure chamber with 100 kg of grinding media (ceramic bearings of 25.4 mm size). The chamber was pressurized to an initial pressure of 448 kPa with flue gas (CO2: 8% by volume-10% by volume; H2O: 18% by volume-20% by volume; O2: 2% by volume-3% by volume; N2: 67% by volume-72% by volume) and rotated on a roller at 38 RPM for 2 days to obtain mechanochemically carbonated clay. The clay precursor was used as is. The reaction was initiated at room temperature and no heating or cooling was applied. The ceramic bearings had an Al2O3 content of 92 wt.%, so that they were also used as catalysts. A portion of the clay precursor was subjected to conventional milling for use as a comparative example. The properties of the milled clay precursor (D1) and the obtained mechanochemically carbonated clay (D2) are shown in the following table. Sample E

[0131] Mechanochemically carbonated clay was produced by inserting 1 kg of clay precursor (shale raw material, non-calcined) (which was pre-treated by calcination (1000° C.) and conventional milling) into a pressure chamber with 17.5 kg of milling media (ceramic bearings of 10 mm size). The chamber was pressurized to an initial pressure of 441 kPa with flue gas (CO2: 8%-10% by volume; H2O: 18%-20% by volume; O2: 2%-3% by volume; N2: 67%-72% by volume) and rotated on a roller at 38 RPM for 2 days to obtain mechanochemically carbonated clay. The reaction was initiated at room temperature and no heating or cooling was applied. The ceramic bearings had an Al2O3 content of 92 wt.%, so that they were also used as catalysts. The properties of the milled and calcined clay precursor (E1) and the obtained mechanochemically carbonated clay (E2) are shown in the following table.

[0132] For sample A, the BET surface areas of the precursor and the carbonated material were determined to be 6.6 m 2 / g and 24.9m 2 / g, indicating that a large part of the surface area increase achieved by the method of the present invention can be attributed to the change in pore surface area.

[0133] As can be observed from the Strength Activity Index (SAI) measurements and the Water Demand measurements, the mechanochemically carbonated clay of the present invention provides unexpectedly reduced water demand and increased strength compared to untreated clay, compared to ground clay, compared to calcined clay, and compared to a Portland cement control.

Claims

1. A mechanochemically carbonated clay obtainable by carbonation of a clay precursor, wherein: The mechanochemically carbonated clay has a thickness of less than 50 m 2 / g specific surface area, and among them, the ratio of the CO2 content of the mechanochemically carbonated clay to the CO2 content of the clay precursor is at least 1.1:1, preferably at least 1.15:1, more preferably at least 1.2:1, wherein the CO2 content is determined as the mass loss above 450°C measured by TGA using a temperature trace in which the temperature is increased from room temperature to 800°C at a rate of 10°C / min; and / or • The ratio of the total carbon content of the mechanochemically carbonated clay to the total carbon content of the clay precursor is at least 1.3:1, more preferably at least 1.35:

1.

2. The mechanochemically carbonated clay of claim 1, having one, two, or three, preferably all three of the following characteristics: D10 in the range of 0.005-3 μm, preferably 0.01-2 μm, most preferably 0.1-1.4 μm; D50 in the range of 0.1-30 μm, preferably 0.5-15 μm, most preferably 1-10 μm; • D90 in the range of 0.5-100 μm, preferably 1-80 μm, most preferably 5-70 μm.

3. The mechanochemically carbonated clay according to any preceding claim, having a CO2 content greater than 0.8 wt.% (based on the total weight of the mechanochemically carbonated clay), preferably greater than 1 wt.% (based on the total weight of the mechanochemically carbonated clay), wherein the CO2 content is determined as the mass loss above 450°C measured by TGA using a temperature trace in which the temperature is increased from room temperature to 800°C at a rate of 10°C / min.

4. The mechanochemically carbonated clay of any preceding claim having a total carbon content of at least 0.75 wt.%, preferably at least 0.85 wt.%, more preferably at least 0.9 wt.%.

5. The mechanochemically carbonated clay according to any preceding claim, having a strength activity index (SAI) at day 7 determined according to ASTM C311 / C311M-22 of at least 105%, preferably at least 110%, even more preferably at least 125% and having a strength activity index (SAI) at day 28 determined according to ASTM C311 / C311M-22 of at least 110%, preferably at least 115%, even more preferably at least 125%.

6. A method for producing mechanochemically carbonated clay, the method comprising the following steps: a) providing a raw material comprising a clay precursor; b) providing a gas comprising at least 0.5% by volume of CO2; c) introducing the raw material and the gas into a mechanical stirring unit; as well as d) subjecting the feedstock material to a mechanical stirring operation in the presence of the gas in the mechanical stirring unit.

7. The method of claim 6, wherein: The clay precursor is a material having a diameter less than 20 m 2 / g, preferably less than 10m 2 / g, more preferably less than 2m 2 / g of specific surface area of ​​particulate material.

8. The method according to any one of claims 6 or 7, wherein: The gas provided in step (b) is a combustion flue gas, preferably a combustion flue gas from the combustion of fossil fuels, the combustion of wood pellets, the combustion of biomass or the combustion of municipal waste.

9. The method according to any one of claims 6 to 8, wherein: This step (d) is carried out as follows: at a pressure of less than 10000 kPa, preferably less than 5000 kPa, more preferably less than 2500 kPa and most preferably less than 1000 kPa; and - At a temperature of less than 150°C, preferably less than 100°C.

10. The method according to any one of claims 6 to 9, wherein: The feedstock provided in step (a) is a solid feedstock having a moisture content of less than 30 wt.% (based on the total weight of the solid feedstock), preferably less than 20 wt.%, more preferably less than 15 wt.%.

11. The method according to any one of claims 6 to 10, wherein: Carbonation, size reduction and / or surface area increase are achieved during step (d) such that the ratio of the total carbon content of the mechanochemically carbonated clay obtained in step (d) to the total carbon content of the clay precursor of step (a) is at least 1.3:1, more preferably at least 1.35:1, and such that the process has one, two, or all three, preferably all three, of the following characteristics: the ratio of the CO2 content of the mechanochemically carbonated clay obtained in step (d) to the CO2 content of the clay precursor of step (a) is at least 1.1:1, preferably at least 1.15:1, more preferably at least 1.2:1, wherein the CO2 content is determined as the mass loss above 450°C measured by TGA using a temperature trace in which the temperature is increased from room temperature to 800°C at a rate of 10°C / min; the ratio of the D50 of the mechanochemically carbonated clay obtained in step (d) to the D50 of the clay precursor of step (a) is less than 0.9:1, preferably less than 0.85:1, more preferably less than 0.8:1; • The ratio of the specific surface area of ​​the mechanochemically carbonated clay to the specific surface area of ​​the clay precursor is at least 1.15:1, preferably at least 1.2:1, more preferably at least 1.25:

1.

12. The method according to any one of claims 6 to 10, wherein: The mechanochemically carbonated clay obtained in step (d) has a water demand determined according to ASTM C311 / C311M-22 of less than 93%, preferably less than 91%.

13. A mechanochemically carbonated clay obtainable by the method according to any one of claims 6 to 12.

14. A composition comprising the mechanochemically carbonated clay as claimed in any one of claims 1 to 5 or 13 and an additional material selected from the group consisting of: asphalt, geopolymers, cement, polymers and combinations thereof, preferably cement, more preferably Portland cement.

15. A method for preparing concrete or mortar, the method comprising the following steps: (i) providing a mechanochemically carbonated clay as claimed in any one of claims 1 to 5 or 13 and a further material selected from the group consisting of asphalt, cement, geopolymers and combinations thereof, optionally in the form of a composition as described in claim 14, wherein the further material is selected from the group consisting of asphalt, cement, geopolymers and combinations thereof; (ii) providing construction aggregates; (iii) contacting, preferably mixing, the mechanochemically carbonated clay of step (i) and the further material with the building aggregate of step (ii) and optionally water.

16. Use of the mechanochemically carbonated clay according to any one of claims 1 to 5 or 13: as a filler, preferably as a filler in a material selected from the group consisting of asphalt, cement, geopolymer, mortar, polymer and combinations thereof; As a partial replacement for asphalt, geopolymer, or cement in concrete or mortar; Increase the compressive strength of concrete or mortar; Improve the durability of concrete or mortar; Improve the durability of concrete or mortar by reducing chloride permeability and / or porosity; Reduce the expansion of concrete; Improve the strength activity index of concrete or mortar; and / or Reduce the water demand of concrete or mortar, Preferably, · Simultaneously improve the strength activity index of concrete and reduce the water demand of concrete; or · Simultaneously improve the strength activity index of the mortar and reduce the water demand of the mortar.

Citation Information

Patent Citations

  • Portland limestone calcined clay cement

    US20120055376A1